Eksistensi Kearifan Lokal Desa Adat Tenganan Pegringsingan dalam Pembangunan Hukum Lingkungan yang Berkelanjutan: Penelitian - I Gede Druvananda Abhiseka; Putu Wahyu Widiartana; Febriansyah Ramadhan; Ni Putu Ega Maha Wiryanthi; I Putu Edi Rusmana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the existence and implementation mechanisms of local wisdom in environmental management within the Tenganan Pegringsingan Traditional Village, Karangasem Regency, Bali, as a form of customary law application contributing to the development of sustainable environmental law. This research is motivated by the increasing challenges to environmental preservation caused by rapid development and tourism, which potentially displace the traditional values of indigenous communities. The study employs a qualitative method using a descriptive approach through stages of observation, in-depth interviews with customary leaders and community members, as well as documentation of awig-awig (customary regulations) and local socio-cultural practices. The findings reveal that Tenganan Village possesses a robust customary legal system, as reflected in awig-awig that strictly regulate the use of natural resources, including prohibitions against cutting trees in sacred forests, restrictions on land ownership, and collective systems for water and forest management. The local wisdom rooted in the Tri Hita Karana philosophy fosters a harmonious and sustainable relationship between humans and nature.